The Effect of Cell Dose on the Early Magnetic Resonance Morphological Outcomes of Autologous Cell Implantation for Articular Cartilage Defects in the Knee: A Randomized Clinical Trial. (August 2016) - Niemeyer, Philipp; Laute, Volker; John, Thilo; Becher, Christoph; Diehl, Peter; Kolombe, Thomas; Fay, Jakob; Siebold, Rainer; Niks, Milan; Fickert, Stefan; Zinser, Wolfgang
Background: Although autologous chondrocyte implantation (ACI) has been established as a standard treatment for large full-thickness cartilage defects, the effect of different doses of autologous chondrocyte products on structural outcomes has never been examined. Hypothesis: In ACI, the dose level may have an influence on medium-term magnetic resonance morphological findings after treatment. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 75 patients who underwent ACI using a pure, autologous, third-generation matrix-associated ACI product were divided into 3 groups representing different doses: 3 to 7 spheroids/cm 2, 10 to 30 spheroids/cm 2, and 40 to 70 spheroids/cm 2 . Magnetic resonance imaging was performed at 1.5, 3, 6, and 12 months after ACI and was evaluated by the magnetic resonance observation of cartilage repair tissue (MOCART) score and the Knee injury and Osteoarthritis Outcome Score (KOOS). Results: MOCART scores showed improvements after 3 months, with slight dose dependence, and further improvement after 12 months, although without significant dose dependence. The mean MOCART scores after 3 months (0 = worst, 100 = best) were 59.8, 64.5, and 64.7 for the low-, medium-, and high-dose groups, respectively, and 62.9 for all patients; at 12 months, these were 74.1, 74.5, and 68.8 for the respective dose groups and 72.4 for all patients. Several MOCART items (surface of repair tissue, structure of repair tissue, signal intensity of repair tissue, subchondral bone, and synovitis) showed a more rapid response with the medium and high doses than with the low dose, suggesting a potential dose relationship. No significant correlation between the MOCART (overall and subscores) with clinical outcomes as assessed by the overall KOOS was detected at 3- and 12-month assessments. Conclusion: This study reveals a trend toward earlier recovery after treatment with higher spheroid doses in terms of better defect filling for full-thickness cartilage defects of the knee, while outcomes after 12 months were similar in all dose groups. However, a correlation with clinical outcomes or the failure rate at 1 year after ACI was not found. A longer follow-up will be required for more definite conclusions on the clinical relevance of ACI cell density to be drawn. Registration: NCT01225575 (ClinicalTrials.gov identifier); 2009-016816-20 (EudraCT number).